THE APPLICATION OF AGRI-FISHERY SYSTEM IN FARMER GROUPS OF AR-RAHMAN TALANG’S VILLAGE DISTRICT WEST PAYAKUMBUH PAYAKUMBUH CITY WEST SUMATERA PROVINCE - Pramudia, Hegiandi; Hamid, Hamdi; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted in February 2014 held at the farmer group of Ar-Rahman. The research location was determined intentionally, the method that used was asurvey by analyzing primary data, the respondents in this research were selected bypurposive sampling with the number of respondents as many as 7 peoples. The purpose ofthis research was to knowing the application of agri-fishery system in farmer group of Ar-Rahman, knowing the development of each subsystem, and knowing the constraints in theimplementation of each subsystem in farmer group of Ar-Rahman.Application of agri-fishery system in farmer group of Ar-Rahman on the inputsupply subsistem has been running well, the farming subsystem is not good, theagroindustry subsystem is not bad, and the marketing subsystem is good. The developmentof agri-fishery system at a standing start in 2007 to 2010 has been running well, but in2011 the start of the conflict in the farmer group has made the farmer group of Ar-Rahmandeclined in each of subsystems until the 2014’s. Constraints in the input supply subsystemis a farmer group can not make food of the fish. Constrainst in the farming subsystem isthe irrigation which is often problematic when the rains come and the limited skills ofmembers to handling cultivation. In the agroindustry subsystem are constrainst on the lackof skills to use a fish processing tool. In the marketing subsystem does not happenconstraints, but is highly dependent on the production of farming and agroindustry.